SOME ISSUES OF PARLIAMENTARY CONTROL OVER THE STATE BUDGET IN THE CONSTITUTION LEGAL ORDER - Sardorbek Yusupov (International Scientific and Current Research Conferences, 2021)
This report provides scientifically based information on the fact that the relations of parliamentary control over the state budget are regulated at the constitutional level, as well as the emergence of the constitutional basis of parliamentary control over the state budget in foreign countries.